2009
DOI: 10.1007/s00442-009-1494-7
|View full text |Cite
|
Sign up to set email alerts
|

Induced resistance in a brown alga: phlorotannins, genotypic variation and fitness costs for the crustacean herbivore

Abstract: In the marine littoral, strong grazing pressure selects for macroalgal defenses such as the constitutive and inductive production of defense metabolites. Induced defenses are expected under spatiotemporally varying grazing pressure and should be triggered by a reliable cue from herbivory, thereby reducing grazing pressure via decreased herbivore preference and/or performance. Although induced resistance has frequently been demonstrated in brown macroalgae, it is yet to be investigated whether induced macroalga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
29
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 56 publications
6
29
0
Order By: Relevance
“…Previous studies on the A. nodosum algal model have shown that waterborne signaling affects the population dynamics of herbivores and predators in controlled laboratory conditions [21] [53]. It has also recently been suggested that resistance to herbivores may be induced in advance by waterborne cues and spread effectively throughout a F. vesiculosus belt [23]. In diatoms, perception of sublethal levels of aldehydes such as (2E,4E/Z)-decadienal by cells close to damaged cells could sensitize resistance to successive aldehyde exposure, providing an early-warning protective mechanism, as shown by Vardi et al [54].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies on the A. nodosum algal model have shown that waterborne signaling affects the population dynamics of herbivores and predators in controlled laboratory conditions [21] [53]. It has also recently been suggested that resistance to herbivores may be induced in advance by waterborne cues and spread effectively throughout a F. vesiculosus belt [23]. In diatoms, perception of sublethal levels of aldehydes such as (2E,4E/Z)-decadienal by cells close to damaged cells could sensitize resistance to successive aldehyde exposure, providing an early-warning protective mechanism, as shown by Vardi et al [54].…”
Section: Discussionmentioning
confidence: 99%
“…This phenomenon is especially well documented in freshwater ecosystems [18] [19]. In marine benthic communities, this type of communication has been reported in rockweed ( Ascophyllum nodosum ) — a common brown alga of North Atlantic rocky shores — when it interacts with an herbivorous snail [20] [21] as well as in other species of fucoids challenged with crustacean grazers [22] [23]. Little is known about the chemical structure of these waterborne cues and the steps that lead from their perception to the actual defense response [20], which may express its features only after a secondary attack.…”
Section: Introductionmentioning
confidence: 85%
“…These patterns were observed at both European shores and were almost identical between assays using fresh and reconstituted seaweeds. Although the nature of the water-borne risk cues mediating trophic interactions between grazers and seaweeds is still unknown, several other studies working on seaweed-seaweed interactions assumed water-borne cues to evolve as signals in aquatic environments [18], [29], [30].…”
Section: Discussionmentioning
confidence: 99%
“…Quantitative variation in the concentration of secondary metabolites is common, and occurs over a range of spatial and temporal scales (Van Alstyne et al 2001a). This variation can be generated by heritable differences between individuals (Wright et al 2004, Haavisto et al 2010 or by environmental factors, such as nutrient concentrations, herbivory, light, and temperature (Karsten et al 1992, Yates & Peckol 1993.…”
Section: Introductionmentioning
confidence: 99%